Renal abscessation in dromedary camels: Clinical, ultrasonographic, hematobiochemical, and etiological investigations - Mohamed Tharwat; Hazem M. M. Elmoghazy; Elhassan M. A. Saeed; Abdulrahman A. Alkheraif (Open Veterinary Journal)
Background: Although renal abscessation is rarely reported in dromedary camels, it is increasingly detected in this species.